Physical properties and antibacterial activity of cotton fabric treated with methanolic extracts of Solanum incanum fruits and red onion peels. Issue 2 (1st February 2022) - Gesese, Tesfa Nega; Workneh Fanta, Solomon; Mersha, Desalegn Abera; Satheesh, Neela
Abstract: The objective of this study is to assess the effect of Solanum incanum fruit (SIFE) and red onion peel (ROPE) extracts treatments on cotton fabric properties. The two factor factorial design was used, the first factor is concentration of the methanolic extract with two levels (3 g/l and 5 g/l) and the second is combination of extracts (25:75 SIFE: ROPE; 50:50 SIFE: ROPE; 75:25 SIFE: ROPE, 100% SIFE, 100% ROPE). Each extract was applied separately and in combination of different proportions on cotton fabric by the pad-dry-cure method using citric acid as a cross-linking agent. After treatment, the physical properties antimicrobial, wash durability and structual properties were determined. Air permeability, water absorbency and tensile strength were decreased for the treated fiber compared with control. Among all treatments, the cotton fabric treated with 50:50 combination was found best in bacterial reduction. This study concluded that, the natural source can sucessfully replace with synthetic chemicals.